2011
DOI: 10.1103/physreva.84.033612
|View full text |Cite
|
Sign up to set email alerts
|

Local atom-number fluctuations in quantum gases at finite temperature

Abstract: We investigate the number fluctuations in small cells of quantum gases pointing out important deviations from the thermodynamic limit fixed by the isothermal compressibility. Both quantum and thermal fluctuations in weakly as well as highly compressible fluids are considered. For the two-dimensional (2D) superfluid Bose gas we find a significant quenching of fluctuations with respect to the thermodynamic limit, in agreement with recent experimental findings. An enhancement of the thermal fluctuations is instea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
106
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(109 citation statements)
references
References 22 publications
3
106
0
Order By: Relevance
“…Therefore, the quantum contribution becomes negligible as ∆ → ∞, and the thermodynamic prediction of Eq. (1) is recovered [25]. For our parameters, the contribution of Eq.…”
Section: Nearly Ideal Bose Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the quantum contribution becomes negligible as ∆ → ∞, and the thermodynamic prediction of Eq. (1) is recovered [25]. For our parameters, the contribution of Eq.…”
Section: Nearly Ideal Bose Gasmentioning
confidence: 99%
“…Although the two-body correlation function g (2) is dominated by quantum fluctuations in this regime, we have shown that the variance δN 2 is still dominated by thermal excitations. To resolve quantum fluctuations one would need to access wavelengths smaller than the phonon thermal wavelengthh 2 /mk B T l ξ [25], which is in the submicron range for our parameters. Our work opens up further opportunities in the study of 1D Bose gases, such as better understanding of the mechanisms of thermalisation and the role of three-body correlations.…”
Section: Nearly Ideal Bose Gasmentioning
confidence: 99%
“…In practice the smallest spot sizes obtained are comparable to the healing length (typically ∼1 μm). The size of the cell relative to the physical length scales of the system (e.g., thermal wavelength and healing length) is crucial in determining the measurement results [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work [23] has addressed how this can be done in uniform systems. Here we consider the extension to the trapped system.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental in situ investigations of atomnumber fluctuations have already probed quantum fluctuations in one dimension [45], the universality of the Berezinkskii-Kosterlitz-Thouless transition [10] and the Hanbury Brown-Twiss effect [46] in Bose gases. Furthermore, recent Theoretical studies pave the way for experi-ments to utilize number fluctuations to investigate spinor condensates [47] and roton excitations in dipolar condensates [48][49][50].…”
Section: Introductionmentioning
confidence: 99%